Pertanggung Jawaban Pidana Korporasi Dalam Kejahatan Ekonomi - Chan, Muhammad Rafly; Prakasa, Ragil Surya; Musa, Muhammad Ibrahim; Pratama, Harits Surya; Al-Qalil, Muhammad Hafisz; Suwanda, Dwi Ari (ASOSIASI IDEBAHASA KEPRI, 2024)
The development of economic globalization has the potential for crime/crimes in the economic sector to be committed by business actors in the form of corporations which can cause losses and victims, which is supported by the emergence and development of science and information technology. The difficulty of holding corporations criminally liable for money game activities by using gold as an object in online investment, using multi-level marketing networks and online networks, ultimately results in material losses for victims as customers. However, criminal liability in the form of strict liability can provide a solution to this problem, where full corporate criminal liability (strict liability) states that criminal liability can be sought against the corporation. This research is normative juridical legal research using a conceptual approach, statutory approach and case approach. Collecting material through literature study methods, with primary or secondary laws. Legal material is further examined and analyzed using the approach used in this research to answer the legal problems in this research. The results of this research show: corporate crime is organized crime which not only involves the corporation itself but also involves organs or administrators in the company. Under this regulation, you unknowingly violate the principle of nebis in idem. So in terms of criminal liability against unincorporated companies the law often decides not only against the company but also against its administrators.